Pelaksanaan Kem Bestari Solat (KBS) program j-QAF di sekolah-sekolah rendah zon Pengerang, Johor - Salai, Nor Azlan (2013)
Various efforts towards strengthening and preservation of the faith students have made through the curriculum and co-curricular activities of Islamic education. Among the aspects that were emphasized in Islamic education system in Malaysia is the practice of prayer among students. Prayer has a very important position in Islam. Prayer is the second pillar of Islam which is also the basis of religion or pole. Establish and practice prayer is submission and obedience to Allah as a Muslim. Thus, the introduction of the Kem Bestari Solat (KBS) activities through the j-QAF program is an approach that was introduced by the Ministry of Education to encourage and develop students to be able complete his prayer in their daily lives. The purpose of this study was to review the implementation of the KBS j-QAF program in Primary Schools in Zone Pengerang, Johor. The study involved teachers in j-QAF fourteen primary schools in Zone Pengerang. Aspects of the study are perceptions, practices and problems faced by the teachers on the implementation of the KBS ever conducted in Schools study. Data were collected through questionnaires. All data were analyzed using Statistical Package For The Social Sciences (SPSS) version 16.0. The findings showed the perception of teachers on the implementation of the KBS high mean value of 4.11. Similarly, the level of teacher practices mean value of 3.97. While the problem of the simple mean value of 3.40. The result of t-test for all constructs of the perception study, practice and problem pointed out there is no significant difference between the perception of a teacher p = 0.951 > a 0.05, the level of teacher practices p = 0.834 > a 0.05, and teachers p = 0.347 > a 0.05 on the implementation of KBS by gender. At the end of this study the author also provided some suggestions for improvements.